The Erosion of the German Middle Class - Gerhard Bosch; Thorsten Kalina (Intereconomics, 2016)
Since the mid-1990s, income inequality has increased more sharply in Germany than in many other European countries, as the economic basis of middle-class prosperity and security has crumbled. The new minimum wage, an increase in coverage by collective agreements, the re-regulation of atypical employment forms and the elimination of incentives to take marginal, part-time jobs are the keys to strengthening the middle-income groups in Germany.
Keywords: 330; Einkommensverteilung; Mittelschicht; Mindestlohn; Atypische Beschäftigung; Teilzeitarbeit; Arbeitsmarktpolitik; Deutschland